Overview of catalyst application in petroleum refinery for biomass catalytic pyrolysis and bio-oil upgrading. Issue 107 (16th October 2015) - Ma, Zhongyi; Wei, Lin; Zhou, Wei; Jia, Litao; Hou, Bo; Li, Debao; Zhao, Yongxiang
Abstract : Because there are some similarities in the reaction pathway and feedstock, the success and lessons of catalyst applications in petroleum refinery may help to make a breakthrough in biomass conversion. Abstract : Biomass is considered as an alternative source to fossil fuels for production of renewable liquid fuels and chemicals. Biomass fast pyrolysis integrated with bio-oil catalytic upgrading for liquid biofuel production has attracted much attention in recent years. Catalysts play critical roles in this process. Although many efforts have been made, the selectivity and deactivation of catalysts still remain challenges. Various catalysts have achieved great success and led to significant improvements in petroleum refining processes. The success and lessons of catalyst applications in petroleum refinery may help to make a breakthrough in biomass conversion, because there are some similarities in the reaction pathway and feedstock of the two processes. In this review, several catalysts used in petroleum refining and biofuel production are summarized and compared. Additionally, their functions and applications are discussed. The possibility of applying petroleum refining catalysts in catalytic pyrolysis and catalytic bio-oil upgrading processes are explored. The challenges and opportunities of petroleum refining catalysts for biofuel production are also summarized.